Seroprevalence of Toxoplasmosis among Women Referring to Shahid Beheshti Hospital, Hamadan, Iran - Hamidi, Masoud; Khulojini, Mahdi; Azizian, Reza; Bashiri, Hamed; Ahanchian, Alireza; Babanejad, Mehran; Khayat-Salighehdar, Hatef; Ahmadi, Nayebali (Novelty in Biomedicine, 2015)
Background: Toxoplasmosis is a parasitic disease caused by the protozoan Toxoplasma gondii. The aim of this study was investigate the prevalence of toxoplasmosis among young women who referred to check up for toxoplasmosis attended in Shahid Beheshti hospital, Hamadan during 2013-2014. Materials and Methods: This study was performed on 2523 pregnant women who referred to laboratory of Shahid Beheshti hospital in Hamadan province (western of Iran) during 2013-2014. Age, level of education and place of residence were recorded in the relevant forms. Antibodies serum levels for all samples were examined by ELISA. IgG titer equals and more than 1:200 was presumed as seropositive. Data were analyzed using by SPSS version 19.0 software. Results: 26.1% of IgG seropositive persons were city residents while 32.3% of them lived at village and suburb of city. 1.4% and 1.1% of at risk persons (based on IgG titration) were city and village residents, respectively. 1.3% and 1.9% of IgM seropositives were city and village residents, respectively. The percentage of at risk persons of city and village (based on IgM titration) were 0.3% and 0.6%, in a row. 29.7% of IgG seropositives did not have academic education while 30.4% of them graduated from high school, at least. The seropositive IgM percentage of non-academic educated persons and graduated/academic ones were 1.7% and 1.4%, respectively. Conclusion: Our funding indicates the association between age of women and their level of education with percentage of contamination and prevalence. IgM seropositive is lesser than IgG. It means that toxoplasmosis is chronic or there is previous contact. To avoid the risk of toxoplasmosis infection particularly in pregnant women should be examined and the necessary preventive measures and training for young women should be presented.